Healing words - emotional intelligence, the role of communication in the relationship with hypoacusic children - Stănescu, Nina; Tasențe, Tănase (Technium Social Sciences Journal, 2021)
Wilbur Schramm understands by communication "the process of sending a message and transmitting it in a coded manner using a channel to a recipient for reception". All living bodies communicate with each other, and in society, communication is the paradigm of all human activities; everything that is subscribed to the human being has communicative and communicational connotations. The formation of the individual as a human being can be achieved only in his permanent interaction with others. This interaction is facilitated by the gregarious instinct of man, which is translated into a continuous search for the company of others.